Effect of vascular endothelial growth factor on fibroblasts from external auditory canal cholesteatoma - Naim, Ramin; Chang, Ray C.; Sadick, Haneen; Bayerl, Christiane; Bran, Gregor M.; Hörmann, Karl (Archives of medical research, 2005)
Background - EACC is a disease of the external auditory canal resulting in destruction of adjacent tissue. However, the role of the surrounding mesenchymal fibroblasts of the perimatrix still remains unclear. In this study we treat isolated fibroblasts of EACC with VEGF and determine FGF-2 levels. We also treat the fibroblast cultures with FGF-2 and measured VEGF levels. - Methods - All EACC cell cultures were obtained from five patients undergoing surgery and used at passage 3. After 1-4 days incubation with 50 ng/mL FGF-2, and 1-8 days incubation with 50 pg/mL VEGF incubation, the expression of the FGF-2 and VEGF protein in the supernatants of the HGF/SF-treated and -untreated culture cell lines was analyzed, respectively. - Results - After 8 days of incubation with 50 ng/mL VEGF, the levels of FGF-2 decreased. However, after 4 days of incubation with FGF-2 the VEGF levels increased significantly in treated tissue culture (p <0.05) in comparison to untreated EACC fibroblasts. The total protein concentration showed no significant difference in both cultures (p >0.05). - Conclusions - In summary, exogenous FGF-2 increased fibroblast expression of VEGF, which is a major autocrine mediator of FGF-2-induced angiogenesis and proliferation. However, incubation with VEGF resulted in decrease of FGF-2 levels. Regarding the slow growth of the fibroblasts, they may not be as likely to exhibit a reactive or invasive phenotype as seen in middle ear cholesteatoma fibroblasts.